H∞ Dynamic Output Feedback Control for Asynchronously Switched Systems: Dwell Time Dependent Control Method - Fugui Deng; Haoxu Wang; Jiandong Guo; Boyu Wang; Yongqing Fu; Weizhong Chen (IEEE Access)
This study focuses on the dynamic output feedback control for asynchronously switched systems with a dwell time dependent control scheme. By combining asynchronous switching with mode-dependent hybrid dwell time switching signal, a novel asynchronously control strategy is proposed, and the controller gain can be dynamically adjusted according to the controller-running interval and switching signal, which reduces the conservatism of the existing results. Firstly, grounded in the constructed Lyapunov function, a stability and $\mathcal {L}_{2}$ -gain criterion is presented for the considered system. Then, an arrangement of mode-dependent dynamic output feedback controllers and switching signal are jointly designed to ensure the global uniform exponential stability of switched systems with ${\mathcal {H}}_{∞ } $ performance. At the conclusion, a simulation example is provided to demonstrate the strengths and practicality of the proposed method.